Teologi Struktur Tubuh dan Kesehatan Manusia dalam Perspektif Metode Terapi PAZ - Danni Nursalim; Engkos Kosasih (Jurnal Teologi Islam, 2026)
Bodily health is one of the most important things to discuss in human life. Some studies link the relationship between the structure of the human body and its health. Linking the human body and health to religious teachings is not new and is found in almost all religions in the world. End-of-Days Medicine is a complementary therapy method that looks at the structure of the human body differently, based on the inspiration found in the Qur'an by its inventor, and sees a connection between the structure of the body and human health. This research combines qualitative and quantitative methods to obtain more accurate data, with a literature review and field observation approach. The results show that this type of theology is not something that deviates from religious teachings and is also not something that contradicts science. The understanding of the body structure in the style of the PAZ Therapy Method is interesting for further research, because it is a new paradigm that has never been put forward by health practitioners before and now.